1999
DOI: 10.1046/j.1460-9568.1999.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide Y Y1 receptor is a somatic receptor on dorsal root ganglion neurons and a postsynaptic receptor on somatostatin dorsal horn neurons

Abstract: Using indirect immunofluorescence, neuropeptide Y Y1 receptor (Y1 receptor)-like immunoreactivity (LI) was localized close to the plasmalemma of small neurons in lumbar dorsal root ganglia (DRGs) and neurons in the inner lamina II of the lumbar spinal cord of the rat. Using confocal microscopy, colocalization of Y1 receptor-LI and transferrin receptor-LI, a marker for endosomes and coated vesicles, was observed in dot-like structures along the plasmalemma. Under the electron microscope, Y1 receptor-LI was loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 101 publications
(208 reference statements)
3
38
1
Order By: Relevance
“…The identified PSDC profiles did not co-express fluorescent labeling for parvalbumin, calbindin D, CGRP, substance P, PKCg, NPY and galanin or for the MOR, Y1, NK1 or P2X 3 receptors in either group of animals. The profile found in the present study is consistent with previous observations (Zhang et al 1999;Ossipov et al 2002;Todd, 2002;Gardell et al 2003). Earlier electrophysiologic studies indicated that transmission of visceral nociception to the n. gracilis is mediated through the PSDC neurons (Palecek et al, 2003;Al-Chaer et al 1996a).…”
Section: Discussionsupporting
confidence: 93%
“…The identified PSDC profiles did not co-express fluorescent labeling for parvalbumin, calbindin D, CGRP, substance P, PKCg, NPY and galanin or for the MOR, Y1, NK1 or P2X 3 receptors in either group of animals. The profile found in the present study is consistent with previous observations (Zhang et al 1999;Ossipov et al 2002;Todd, 2002;Gardell et al 2003). Earlier electrophysiologic studies indicated that transmission of visceral nociception to the n. gracilis is mediated through the PSDC neurons (Palecek et al, 2003;Al-Chaer et al 1996a).…”
Section: Discussionsupporting
confidence: 93%
“…In some cells, NPY and [F7, P34]NPY also decreased mIPSC amplitude distributions, suggesting an additional postsynaptic action. This is consistent with reports that Y1 receptors are localized to the dendrites of somatostatin (SST)-positive dorsal horn neurons (Zhang et al 1994a(Zhang et al , 1999. SST-containing neurons in the dorsal horn represent a morphologically heterogeneous population that is composed of both stalked and islet cells (Ribeiro-da-Silva and Cuello 1990;Todd and Spike 1993), some of which are thought to be excitatory interneurons (Todd and McKenzie 1989;Spike and Todd 1992).…”
Section: Y1 Suppression Of Inhibitory Synaptic Transmissionsupporting
confidence: 90%
“…This is consistent with the presence of Y1 receptors on presynaptic inhibitory terminals and likely also postsynaptically on SG neurons. (Zhang et al 1994a(Zhang et al , 1999. FIG. 4.…”
Section: Mechanism Of Y1 Receptor Suppression Of Inhibitory Synaptic mentioning
confidence: 99%
“…Using immunofluorescence, confocal laser microscopy, and electron microscopy, Zhang et al [22] made similar observations concerning the distribution of the Y1 receptor on ganglion neurons. By colocalization of the Y1 receptor and the transferrin receptor in dot-like structures along the plasmalemma and a complex distribution pattern in the cells, they concluded on receptor turnover and internalization.…”
Section: Discussionmentioning
confidence: 78%